The Suluk ethnic group in Sabah, Malaysia: a socio-cultural narrative - Habibah @ Artini Ramlie; Norshahrul Marzuki Mohd Nor; Mohamad Basri Jamal; Aishah Tamby Omar; Saifulazry Mokhtar (Pennwell Corporation, 2020)
The Suluk are one of many ethnic groups found in Sabah, East Malaysia. As is typical of these groups, the Suluk have a rich heritage that is reflected in a fascinating cultural fabric. This study presents a general narrative of ethnic Suluk imagery in Sabah, via a qualitative approach based on archival research of library resources including archival records, books, journals and conference papers discussing the Suluk and their ethnicity. The findings of this study are expected to enhance our understanding of Sabah’s diverse multi-ethnic community by focusing on the Suluk ethnic group.